Kesalahan Penggunaan Kata Kerja “Juyou” dan “Yongyou” dalam Karangan Mahasiswa STBA-PIA Medan Semester VII T.A. 2020/2021 - Sinar Anwar; Yuliandre Wijaya; Kesumawaty Wijaya; Robbert Robbert (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
The aim of this research is to describe the types of language errors and the factors that cause them in the use of the verbs jùyǒu and yōngyǒu in Mandarin essays in the seventh semester of STBA-PIA T.A. 2020/2021. This research uses a qualitative descriptive research design to achieve the research objectives. The subjects of this research were 40 students. The data collection techniques used are documentation techniques to determine the types of language errors and interview techniques to determine the factors that cause these language errors. This research obtained results showing that there were four types of errors made by students of the fourth year Chinese literature study program STBA-PIA Medan semester VII, namely subtraction errors of 1 sentence (1.2%), addition errors of 7 sentences (8 .2%), replacement errors were 74 sentences (87.1%) and sequencing errors were 3 sentences (3.5%), where replacement errors were the highest type of error among the four types of errors. Apart from that, the factors causing errors in using the verbs jùyǒu and yōngyǒu can be divided into two, namely interlingual factors as many as 3 people (30%) and intralingual factors as many as 7 people (70%).